Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel

Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte

Orthorhombic/cubic Cd2SnO4 nanojunctions: enhancing solar water splitting efficiency by the suppression of charge recombination - Deshpande, Aparna; Kelkar, Sarika A.; Rayalu, Sadhana; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
The low practical efficiency of binary metal oxide semiconductor-based photo-electrochemical (PEC) water splitting has prompted researchers to examine ternary and quaternary oxides, which provide more leverage for engineering the desired PEC properties via stoichiometry (valence) and phase control. One ternary system of interest in this context is cadmium tin oxide (Cd2SnO4), which supports the cubic and orthorhombic phases with optical, electronic and catalytic properties that are favourable for PEC water splitting. However, its practical PEC performance is limited by high surface recombination of the photogenerated charge carriers. In this work we circumvent this problem by engineering the constitution of Cd2SnO4 nanoparticles to a biphasic nanojunction form, comprising of a nanocomposite of cubic and orthorhombic phases. The favourable conduction band alignment between the cubic and orthorhombic phases leads to a dramatic reduction in the recombination of the photogenerated charges, leading to a 10-fold increase (from 250 mu A cm(2) to over 2 mA cm(2)) in the photocurrent vis-a-vis the single cubic or orthorhombic phase performance. We discuss the underlying mechanism for the observed dramatic enhancement in the water splitting efficiency.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.

NiS1.97: a new efficient water oxidation catalyst for photoelectrochemical hydrogen generation - Bhosale, Reshma; Kelkar, Sarika A.; Parte, Golu; Fernandes, Rohan; Kothari, Dushyant; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2015)
NiS1.97, a sulfur-deficient dichalcogenide, in nanoscale form, is shown to be a unique and efficient photoelectrochemical (PEC) catalyst for H-2 generation by water splitting. Phase pure NiS1.97 nanomaterial is obtained by converting nickel oxide into sulfide by controlled sulfurization method, which is otherwise difficult to establish. The defect states (sulfur vacancies) in this material increase the carrier density and in turn lead to favorable band line-up with respect to redox potential of water, rendering it to be an effective photoelectrochemical catalyst. The material exhibits a remarkable PEC performance of 1.25 mA/cm(2) vs NHE at 0.68 V in neutral pH, which is almost 1000 times superior as compared with that of the stoichiometric phase of NiS2. The latter is well-known to be a cocatalyst but not as a primary PEC catalyst.
Keywords: dichlacogenide; Faradaic efficiency; Hydrogen generation; NiS1.97; nonstoichiometric; photoelectrochemical catalyst; sulfurization

Quenching effect of uranyl species in the photoluminescence emission and visible-light-driven water dissociation activity of CdS and TiO2 photocatalysts - Gupta, Narendra M.; Kelkar, Sarika A.; Korake, Prakash V. (Photochemical & Photobiological Sciences, 2016)
Anchoring of uranyl species (2-4 mol%) led to the complete quenching of photoluminescence emission and the visible-light-driven water photodissociation activity of TiO2 (Degussa-P25) and a hydrothermally synthesized CdS photocatalyst. Photophysical measurements revealed a fast relaxation and the transfer of photogenerated electrons/energy from the TiO2 or CdS substrate to the acceptor uranyl moieties. Besides the position of flat band levels, significant overlap of the absorption/emission spectra of the host matrix and the surface-bound UO22+ species is responsible for this reverse energy transfer from a wide bandgap semiconductor to a material with a smaller band-to-band energy gap.